Hubungan Pengelolaan Air Minum dan Makanan Rumah Tangga Dengan Kejadian Diare - Ikrimah Ikrimah; Maharso Maharso; Noraida Noraida (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
Abstract: Relation Of Drinking Water Management And Household Food With Diarrhea Occurrence. In Kalimantan Selatan, Kabupaten Hulu Sungai Tengah, Kecamatan Batang Alai Utara, Public Health Center of Ilung is spread of diarrhea. By 2015, the prevalence of diarrhea occurrence in Kecamatan Batang Alai Utara is 2.85% and 2.7% (2016). However, the coverage of access to clean water is only about 28%. Report of KKN Labunganak Village RW. 01 Kecamatan Batang Alai Utara, 67% is not carried out water purification in any way by the community, so it is still possible to be a media water borne disease. In the management of household food, only 13% of food is stored in closed shelves / cabinets, so it can become a food borne disease medium.The purpose of this study was to determine the relation between drinking water and household food management with diarrhea occurrence in the working area Public Health Center of Ilung, Kecamatan Batang Alai Utara. The type of research is observational in the form of analytic, research design that is retrospective approach (case control study). The results showed that there was no relation between drinking water management (p value = 0,300> α = 0,05) and household food (p value = 1,000> α = 0,05) with diarrhea occurrence. It is recommended for further investigators to examine other risk factors as causes of diarrhea and can be continued by examining the different communities as control groups .